G191(P) So you want to be a paediatrician?. (27th April 2015) - Anpananthar, A; Ware, N; Kingdon, C; Klaber, R
Abstract : Background: There are a number of different career pathways facing paediatric trainees including academia, time out of training and subspeciality training. The careers advice they receive is dependent on their trainers and the trainees accessing the available resources and networks. The Royal College of Paediatric and Child Health has careers fairs for recruitment into paediatrics and is currently actively developing its mentoring strategy for paediatricians. The aim of this study was to assess the need for a careers fair Methods: A pilot regional careers evening for level 1 paediatric trainees was held in May 2014. As our level 2 and 3 trainees have the opportunities for peer networking at the existing regional training, this pilot careers evening was only aimed at level 1 trainees. The evening included talks on career pathways and signposting with questions and answer sessions with experts. Anonymous feedback was collated at the end of the event and 5 months post-event. Results: Of the 21 trainees who attended, 27% had not had careers advice to date. 100% found the evening useful and all left with an action plan to explore their career options. Positive free text feedback included 'asking questions in informal manner, with immediate answers'; 'demystifying the Grid/general level 3 process'; 'discussion of different options available'; 'encouraged thinking about career plans'. Of the 47% response to the post-event survey, trainees had sought careers advice from their educational supervisors or tertiary units, had become involved in management activities and looked into out of programme options. All had attributed these actions to the careers evening and most found the evening 'useful' or 'inspiring' . These results were discussed in focus groups, comprised of training programme directors, college tutors, trainee committee members and trust representatives, to shape the programme for the next paediatric careers event. Conclusion: The feedback was overwhelmingly positive with high demand for it to be held annually in our region. It will be open to all paediatric trainees, which will also further enable the senior trainees to provide careers advice in their future roles as educational supervisors and mentors.